Isoniazid: A Review of Characteristics, Properties and Analytical Methods - Fernandes, Guilherme Felipe dos Santos [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Santos, Jean Leandro dos [UNESP] (Taylor & Francis, 2017)
Isoniazid is a synthetic antimicrobial and one of the most important first-line drugs used in the treatment of tuberculosis. Since it was introduced in the therapy in 1952, the drug remains at the front line of the antituberculosis treatment mainly due to its potency and high selectivity against Mycobacterium tuberculosis. Pharmaceutical analysis and therapeutic drug monitoring of isoniazid in both, pharmaceuticals and biological samples, plays an important role to comprehend aspects regarding to bioavailability, bioequivalence and therapeutic monitoring during patients following-up. In the last case, validated and simple methods are extremely useful for Public Healthy in order to guarantee the drug efficacy, safety and reduce the tuberculosis resistance. Among the available analytical tools, HPLC-based methods coupled to ultraviolet or mass spectroscopy are the most widely used techniques to quantify isoniazid. Therefore, this review highlights the main analytical methods reported in the literature for determination of isoniazid focusing in HPLC-based methods.
Keywords: Analytical methods; high performance liquid chromatography; isoniazid; mass spectroscopy; ultraviolet